2020
DOI: 10.15441/ceem.19.052
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 30-day mortality of patients with pneumonia in an emergency department setting using machine-learning models

Abstract: Objective This study aimed to confirm the accuracy of a machine-learning-based model in predicting the 30-day mortality of patients with pneumonia and evaluating whether they were required to be admitted to the intensive care unit (ICU). Methods The study conducted a retrospective analysis of pneumonia patients at an emergency department (ED) in Seoul, Korea, from January 1, 2016 to December 31, 2017. Patients aged 18 years or older with a pneumonia registry designation on their electronic medical record were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…At present, only a few studies have reported the application of machine learning in pneumonia-related studies. And several studies have employed machine learning methods to predict mortality from pneumonia ( Cooper et al, 1997 ; Wiemken et al, 2017 ; Kang et al, 2020 ), while other adverse outcomes have received less attention, especially one-year post-enrollment status. Feng et al built a three-layer fully connected neural network to classify the prognosis of CAP patients with high accuracy and good generalizability by using ML techniques to predict CAP mortality ( Feng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, only a few studies have reported the application of machine learning in pneumonia-related studies. And several studies have employed machine learning methods to predict mortality from pneumonia ( Cooper et al, 1997 ; Wiemken et al, 2017 ; Kang et al, 2020 ), while other adverse outcomes have received less attention, especially one-year post-enrollment status. Feng et al built a three-layer fully connected neural network to classify the prognosis of CAP patients with high accuracy and good generalizability by using ML techniques to predict CAP mortality ( Feng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We Sequential Organ Failure Assessment (SOFA; 0.670, p < 0.001), and q-SOFA (0.642, p < 0.001). 14 Another study by Kang et al 15 recruited 1,732 adult patients with pneumonia in an ED. These investigators also reported that the AUC of their ML model was 0.844, better than CURB-65 with an AUC of 0.615.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of a recent Korean study found that combining procalcitonin level with pneumonia severity index was better at predicting short-term mortality than PCI alone [ 6 ]. There are studies looking at using machine-learning models, using data and algorithms helping computer programs to improve overtime to predict mortality of patients with pneumonia in the emergency department [ 26 ]. Since pneumonia caused by MDRO organisms, such as P. aeruginosa , extended-spectrum beta-lactamase-producing Enterobacteriaceae, or MRSA tends to have a severe course, but is relatively rare, there is an interest in identifying patients at risk for this malady.…”
Section: Recognition Of Severe Cap In the Emergency Departmentmentioning
confidence: 99%